If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y = 0 + 0 Combine like terms: 0 + 0 = 0 2y = 0 Solving 2y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Divide each side by '2'. y = 0 Simplifying y = 0
| -12=11x-45 | | -7/3x-5y | | 32x-435=179 | | 2y=0-(-6) | | x-41=-48 | | -5/6x-4(3/8x+5/4y) | | x-48=-48 | | 3t+2s+4t+1s= | | 2y=0-(-2) | | -1y=0x+10 | | 87-x=135 | | 6(2x)-48=0 | | 2n+6=n+8 | | 2y=0-6 | | x^3+1/8 | | (4x+3)(3y-8)= | | 0x-2y=6 | | 356+56x=-832 | | 2s^2=50 | | -5(x+2)+9=-1 | | x^2-4y^2+4x+8y-16=0 | | 15x+14=2(5y+6) | | 4x+6x=180 | | 2x-4+x=11 | | 3/4x-(8)=25 | | Tn=4n-11 | | -12+x+2x=9 | | 24.6+3.69/4=9.54 | | 4y-6y+9=-2 | | 6+7x=4+2x | | 8+6a=-29+24 | | (3/7/7/3)*5/9 |